Exsolution of Pt Nanoparticles from Mixed Zr/Gd‐CeO2 Oxides for Microbial Fuel Cell‐Based Biosensors - Alex Martinez Martin; Shailza Saini; Anna Salvian; Tarique Miah; Cheuk Yiu Chan; Claudio Avignone Rossa; Siddharth Gadkari; Kalliopi Kousi (Small Science)
Cerium oxide (CeO2) is a widely used catalyst support in electrochemical and catalytic applications due to its ability to form oxygen vacancies and strong metal‐support interactions. However, conventionally prepared CeO2 catalysts often suffer from deactivation due to sintering and poisoning. Incorporating dopants such as gadolinium (Gd) and zirconium (Zr) into its lattice improves oxygen ion mobility, thermal stability, and resistance to poisoning. Platinum (Pt) is a commonly used catalyst for the oxygen reduction reaction in microbial fuel cells for real‐time biochemical oxygen demand monitoring. However, its high cost, scarcity, and susceptibility to fouling and poisoning limit implementation in wastewater treatment plants. This study employs the exsolution method to investigate the formation of Pt nanoparticles from undoped, Zr‐, and Gd‐doped CeO2 matrices. It is shown that the Gd‐doped matrix exhibits the optimal particle characteristics, while electrochemical evaluation in the microbial fuel cells also reveals that it outperforms the other studied materials, in terms of sensitivity and stability. By integrating exsolution with dopant engineering, in an innovative approach, we lower costs, maintain performance, and enhance the operational stability of the cathode material, paving the way for cost‐effective and sustainable applications in biosensing but also other catalytic applications of interest.